Analisis faktor yang berhubungan dengan mengetahui program tes VCT di Indonesia - Edi Purwanto; Revha Salsabila Virgiea Jasmine (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system by infecting white blood cells. Acquired Immune Deficiency Syndrome (AIDS) is the result of HIV infection which causes several symptoms, namely by attacking the immune system. In 2022, the World Health Organization (WHO) estimates that there will be 110,000 (85.000-160.000) people infected with HIV in the Southeast Asia region. The Ministry of Health of the Republic of Indonesia reported the number of cases in January-June 2022 as many as 22.331 people were infected with HIV and more than 4.010 people were infected with AIDS. Transmission of the HIV virus is not like transmission of the Influenza virus. Therefore, Voluntary Counseling and Testing (VCT) services are one way that can be done so that someone can gain access to all services such as information, education, therapy, and psychosocial support regarding HIV/AIDS. Purpose: To analyze factors related to knowledge about VCT testing programs in Indonesia. Method: Cross-sectional study using secondary data taken from the Demographic Health and Welfare Survey, a survey program from the United States Agency for International Development (USAID) which is conducted periodically. The data used are the 2017 SDKI documents and the number of samples used is 61.547 respondents. Data analysis used is the univariate and bivariate chi-square test. Results: Most respondents were aged ≥35 years as many as 42.872 (69.7%) and were male as many as 55.571 respondents (90.3%) with a low level of education as many as 52.265 (84.9%). Most respondents came from urban areas as many as 32.101 (52.2%). Most respondents obtained sufficient information about VCT HIV/AIDS examination as many as 44.523 (72.3%) and respondents did not know about VCT HIV/AIDS examination as many as 34.043 (55.3%). Data analysis shows the age of respondents (p value = 0.625), while the variables gender, education level, type of residential area, and source of information show a p value < 0.05. Conclusion: There is a significant relationship between the variables of gender, education level, area of ​​residence, and availability of information sources on respondents' knowledge of VCT. However, there is no significant relationship between respondents' age and respondents' knowledge of VCT (p value > 0.05). Suggestion: People who have more knowledge about VCT should always share information with others to prevent or handle unwanted things. In addition, for further research, several variables can be added that have the potential to influence knowledge of VCT. Keywords: Factor Analysis; HIV/AIDS; Voluntary Counseling and Testing (VCT). Pendahuluan: Human Immunodeficiency Virus (HIV) adalah virus yang menyerang kekebalan tubuh dengan cara menginfeksi sel darah putih. Acquired Immune Deficiency Syndrome (AIDS) adalah hasil infeksi dari virus HIV yang memunculkan beberapa gejala yaitu dengan menyerang sistem kekebalan tubuh. Pada tahun 2022 World Health Organization (WHO) memperkirakan 110.000 (85.000-160.000) orang tertular HIV di kawasan Asia Tenggara. Kementerian Kesehatan Republik Indonesia melaporkan jumlah kasus pada bulan Januari-Juni 2022 terdapat 22.331 orang tertular HIV dan lebih dari 4.010 orang tertular AIDS. Penularan virus HIV tidak semudah penularan virus Influenza. Oleh karena itu, layanan Voluntary Counselling and Testing (VCT) merupakan salah satu cara yang dapat dilakukan agar seseorang mendapatkan akses ke semua pelayanan seperti informasi, edukasi, terapi dan dukungan psikososial tentang HIV/AIDS. Tujuan: Untuk menganalisis faktor yang berhubungan dengan pengetahuan tentang program tes VCT di Indonesia. Metode: Penelitian cross sectional menggunakan data sekunder yang diambil dari Survei Kesehatan Demografi dan Kesejahteraan yaitu program survei dari United States Agency for International Development (USAID) yang dilakukan secara periodik. Data yang digunakan merupakan dokumen SDKI 2017 dan jumlah sampel yang digunakan sebanyak 61.547 responden. Analisis data yang digunakan adalah univariat dan bivariat uji chi square. Hasil: Sebagian besar responden berusia ≥35 tahun sebanyak 42.872 (69.7%) dan berjenis kelamin laki-laki sebanyak 55.571 responden (90.3%) dengan tingkat pendidikan rendah sebanyak 52.265 (84.9%). Sebagian besar responden berasal dari daerah perkotaan sebanyak 32.101 (52.2%). Mayoritas responden mendapatkan cukup informasi tentang tes VCT HIV/AIDS sebanyak 44.523 (72.3%) dan responden tidak mengetahui tentang tes HIV/AIDS secara VCT sebanyak 34.043 (55.3%). Analisis data menunjukan umur responden (p value = 0.625), sedangkan variabel jenis kelamin, tingkat pendidikan, jenis daerah tempat tinggal, dan sumber informasi menunjukkan p-value <0.05. Simpulan: Adanya hubungan yang signifikan antara variabel jenis kelamin, tingkat pendidikan, daerah tempat tinggal, dan ketersediaan sumber informasi terhadap pengetahuan responden tentang VCT. Namun, tidak ada hubungan yang signifikan antara usia responden dengan pengetahuan responden tentang VCT (p-value > 0.05). Saran: Masyarakat yang lebih mengetahui tentang VCT agar senantiasa membagikan informasi kepada yang lain untuk mencegah atau menangani hal yang tidak diinginkan. Selain itu, bagi penelitian selanjutnya dapat menambahkan beberapa variabel yang memiliki potensi berpengaruh terhadap pengetahuan tentang VCT. Kata Kunci: Analisis Faktor; HIV/AIDS; Voluntary Counselling and Testing (VCT).